EXTERNAL FACTORS INFLUENCING ENGLISH LEARNING ACHIEVEMENT - Azmi, Fiqih Dita; Supriadi, Iwan; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research was descriptive. The purpose of this research was to describe the degree of externalfactors (social factors and economic status) which may influence English achievement of the NinthGrade students of SMP Bumi Khatulistiwa Kubu Raya in Academic year 2017/2018. Theparticipants of this research were 20 students taken purposively from Class A and B. This researchused an indirect and documentary technique to collect the data. The data collecting tool wasquestionnaire. This research used Likert Scale to analyze the data. The research finding showedthat (1) social factor is the most influencing external factor of English learning achievement.Classmate relationship is the main external factor of social factor. The percentage of social factor57.79%. (2) The percentage of economic status is 42.21%. Home facilities is the main influencing external factor of economic status.Keywords: External factors, English achievement, influence.